2015
DOI: 10.1016/j.ebiom.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Latent and Active Tuberculosis Infection Increase Immune Activation in Individuals Co-Infected with HIV

Abstract: In recent years, chronic immune activation and systemic inflammation have emerged as hallmarks of HIV disease progression and mortality. Several studies indicate that soluble inflammatory biomarkers (sCD14, IL-6, IL-8, CRP and hyaluronic acid), as well as surface markers of T-cell activation (CD38, HLA-DR) independently predict progression to AIDS and mortality in HIV-infected individuals. While co-infections have been shown to contribute to immune activation, the impact of latent tuberculosis infection (LTBI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 37 publications
7
71
1
3
Order By: Relevance
“…In a South-African HIV-infected population study, Sullivan et al showed that patients with active TB infection have elevated levels of soluble inflammatory biomarkers associated with monocyte activation, as well as surface markers of T-cell activation compared to HIV− mono-infected individuals [65]. They also presented that co-expression of CD38 and HLA- DR on CD4+ and CD8+ T cells is higher in HIV infected individuals with latent TB compared to those with no TB and raised again the issue about more widespread treatment of HIV patients with LTBI.…”
Section: Cryptococcusmentioning
confidence: 99%
“…In a South-African HIV-infected population study, Sullivan et al showed that patients with active TB infection have elevated levels of soluble inflammatory biomarkers associated with monocyte activation, as well as surface markers of T-cell activation compared to HIV− mono-infected individuals [65]. They also presented that co-expression of CD38 and HLA- DR on CD4+ and CD8+ T cells is higher in HIV infected individuals with latent TB compared to those with no TB and raised again the issue about more widespread treatment of HIV patients with LTBI.…”
Section: Cryptococcusmentioning
confidence: 99%
“…In addition, M. tuberculosis co-infection may contribute to higher levels of systemic immune activation that is associated with HIV-1 disease progression 19,20 , even in the context of latent TB infection (LTBI) 21 . The importance of these phenotypes in driving HIV-1 disease progression is unknown, but based on our understanding of how high viral loads 22 and immune activation 23 can drive immunosuppression, co-infection with M. tuberculosis may accelerate AIDS progression.…”
Section: Introductionmentioning
confidence: 99%
“…CRP also helps the body recognize the presence and severity of infections [46] and is used as an indicator of low-grade inflammation in chronic infections [7, 8] and chronic diseases [9]. In addition, CRP responds to a variety of maternal factors.…”
Section: Introductionmentioning
confidence: 99%